Cereal Grains - Volume 2 2021
DOI: 10.5772/intechopen.97157
|View full text |Cite
|
Sign up to set email alerts
|

Irrigated and Rain-Fed Lowland Rice Breeding in Uganda: A Review

Abstract: Since introduction of rice into Uganda in 1904, improvement of the irrigated and rain-fed lowland types was undertaken to address a number of production and quality constraints in three consecutive and overlapping phases. The initial phase was achieved through evaluation of introduction, selection of promising lines and subsequent release of the selected lines for production by the farmers. In the second phase, genetic potential of traits and characteristics of interest were analyzed and used to guide selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Studies conducted in Uganda revealed that genotypes MET 3, SUPA 1052, Namche 1, ART-4 and BASMATI 370 exhibited stable 2AP levels. These genotypes were recommended for further use in breeding programs for aroma improvement [79]. Aroma is the main rice characteristic that guides the adoption of varieties, especially in Kenya and Tanzania.…”
Section: Development Of Aromatic Drought-tolerant Rice Varietiesmentioning
confidence: 99%
“…Studies conducted in Uganda revealed that genotypes MET 3, SUPA 1052, Namche 1, ART-4 and BASMATI 370 exhibited stable 2AP levels. These genotypes were recommended for further use in breeding programs for aroma improvement [79]. Aroma is the main rice characteristic that guides the adoption of varieties, especially in Kenya and Tanzania.…”
Section: Development Of Aromatic Drought-tolerant Rice Varietiesmentioning
confidence: 99%